If it's not what You are looking for type in the equation solver your own equation and let us solve it.
26-6x=6
We move all terms to the left:
26-6x-(6)=0
We add all the numbers together, and all the variables
-6x+20=0
We move all terms containing x to the left, all other terms to the right
-6x=-20
x=-20/-6
x=3+1/3
| 4y^2+17y+14=0 | | y/4+y/3=14 | | 2n+43=203 | | 2x+43=203 | | 2x=43=203 | | (3*x)*(5*x)=24 | | x+16/4=8 | | -55=1-7x | | 5(x/6)=1/4 | | 7+2x^/3=5 | | 7=2u-13 | | 5t-12=2t+15 | | Z-3/5=z+5/6 | | 2(y-5)=4(y-4) | | (k+9)=289 | | 9a*2+a2=90 | | 3g+9=23 | | 3a*a2=36 | | 3a*2a=18 | | 20x×3=40 | | 1/n+6-2n-4/5n^2+36=1/5n+6 | | x/x-8=-5/x+5 | | 3w+9-9=18-9 | | 9/x-6=4x | | 3(7a×9)8=100 | | x/2-2(x-5)=1 | | 12=144-n*4 | | 2(v-4)=-4v+4 | | 10(x+6)+x+18=2 | | 8y-5=2y+37 | | 4a(2a+4)=2a(49+4) | | 7n+8=2n+38 |